The dream anatomy between prohibitions and prejudices - Giardina, Simona; Refolo, Pietro; Spagnolo, Antonio G. (Medicina e Morale, 2021)
A large body of international literature agrees that anatomical dissection is irreplaceable for the education of both medical and surgical students. However, as it happened several times in the past, the problem of supplying cadavers persists. Recently, Italy has filled a legal vacuum, and it has passed a law (Law no. 10 of 10 February 2020) on the disposal of one's own body and post-mortem tissues for study purposes. The aim of this contribution is to provide a brief historical overview of the practice of anatomical dissection in its gradual development around a closely related theme, namely the way of conceiving the human body. The ultimate aim is to underline the importance it has always had for medical education.